2022
DOI: 10.26655/jmchemsci.2022.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction: The apt description of COVID-19's clinical course throughout hospitalization provides experiences for dealing with subsequent outbreaks, especially in patients with severe COVID-19 who get admitted to the intensive care unit (ICU). This study aimed to evaluate the symptomatology of patients with COVID-19 admitted to the ICU of Peymaniyeh Hospital in Jahrom in the first to the fifth wave of coronavirus. Methods: This study was a descriptive-analytical on all ICU admitted COVID-19 patients during d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It was reported that pre-existing hypertension as a comorbid condition for older patients with COVID-19 infection [4]. A study of COVID-19 patients admitted during outbreaks in a city of Iran, hypertension was a comorbidity that had no impact on hospitalization course [5]. Even hypertensive cases presented with GI symptoms of COVID-19 had a similar course of hospitalization and the outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that pre-existing hypertension as a comorbid condition for older patients with COVID-19 infection [4]. A study of COVID-19 patients admitted during outbreaks in a city of Iran, hypertension was a comorbidity that had no impact on hospitalization course [5]. Even hypertensive cases presented with GI symptoms of COVID-19 had a similar course of hospitalization and the outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations range from mild flue like symptoms to severe organ dysfunction [4][5][6]. According to the World Health Organizations (WHO), the disease is classified into 4 degrees based on severity: Grade 1: Feeling sick, Grade 2: Cold-like symptoms, runny nose, low-grade fever, low-grade cough, Grade 3: Flu-like symptoms, i.e., fever and chills, loss of appetite and muscle aches, and grade 4: Symptoms of acute respiratory distress syndrome [ARDS], severe Dyspnea, dry cough, and sometimes fever [7]. It has been found that the severity of symptoms is affected by different baseline biological and sociodemographic factors and current health status [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 variants have evolved during the years passing the pandemic and various differences in pattern of disease with various symptoms ranging from classic symptoms of fever and pulmonary symptoms to extrapulmonary ones [2,3]. Likewise, its epidemiological findings [4] have been emerged. In case of transmissibility, Omicron variant is more transmissible than the Delta variant [5].…”
Section: Introductionmentioning
confidence: 99%